(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
A cross sectional study was carried out within the lateral cephalograms on 100 Chinese teenage patients at the department of orthodontia in the second affiliated hospital of Dalian Medical University, CHINA in order to evaluate the Wits measurement as compared to ANB angle for identifying the anteroposterior skeletal discrepancy between maxilla & mandible and to determine the normal Wits value suitable for Caucasian descent whether it was applicable or not on the Chinese teenagers distributed according to sex, age & malocclusion variations. Non probability (purposive) sampling technique to collect 100 samples of lateral cephalometric radiographs and data were collected from the measurements of multiple planes & angles formed by adjoining various anatomic landmarks connecting to each other in those radiographs. Lateral cephalograms of those 100 subjects were divided according to gender, age & malocclusion type. In the sex group there were 43 males & 57 females. In the age group 68 patients ages were from 13 to 15 years and 32 patients ages were from 16 to 19 years. In the malocclusion group 41 patients had class I, 40 patients had class II & 19 patients had class III malocclusions. Statistical analyses were done by t-test (two independent samples) to detect the differences between two sex groups and also between the two age groups. One way ANOVA (analysis of variance) was applied to evaluate the differences of malocclusion classification. The results were statistically significant when p<0.05. Few results were also significant when compared to the level of p<0.01. Sex group showed statistically significant differences of some values like UFH, LFH, TFH & SN. Age group showed statistically significant values in case of LFH & L/TFHP. Malocclusion group showed significant value only for SNA. The research revealed that international Wits value of -1.0 mm for males could be applicable to the males of Chinese teenagers as their average Wits measurements were also found the same in this study. But the international standardized Wits value of 0.0 mm for females couldnt be applicable for Chinese teenage females as their mean value of Wits measurements was found to be -1.2 mm in this study probably due to the slight maxillary retrognathism of Chinese female descents. On the other hand the difference between the Wits appraisal of Chinese male & female teenagers was found to be -0.2 mm which couldnt be considered as a major difference between them. So the normal existence of the Caucasian Wits value of a one mm discrepancy should be modified to -0.2 mm if we want to apply this on teenage patients of Chinese population. DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16588 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 6-11